2021
DOI: 10.2196/23920
|View full text |Cite
|
Sign up to set email alerts
|

Novel Analgesic Index for Postoperative Pain Assessment Based on a Photoplethysmographic Spectrogram and Convolutional Neural Network: Observational Study

Abstract: Background Although commercially available analgesic indices based on biosignal processing have been used to quantify nociception during general anesthesia, their performance is low in conscious patients. Therefore, there is a need to develop a new analgesic index with improved performance to quantify postoperative pain in conscious patients. Objective This study aimed to develop a new analgesic index using photoplethysmogram (PPG) spectrograms and a co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, a key challenge in the success of DL models is the need for large amounts of training data, as the data increases, a well-behaved performance model can be obtained 115 . This in part may explain why most ML models outperformed DL models using the same dataset 35 , 39 or with the use of the same sensor modality 117 , 118 . In many cases, large datasets (in particular, labelled datasets) may be too difficult or costly to be collected for many learning problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a key challenge in the success of DL models is the need for large amounts of training data, as the data increases, a well-behaved performance model can be obtained 115 . This in part may explain why most ML models outperformed DL models using the same dataset 35 , 39 or with the use of the same sensor modality 117 , 118 . In many cases, large datasets (in particular, labelled datasets) may be too difficult or costly to be collected for many learning problems.…”
Section: Discussionmentioning
confidence: 99%
“…In automated pain assessment, these differences have shown an adverse effect in the modelling of both neural and physiological signals for the assessment of pain. In the reviewed literature, several studies using neural (EEG, fNIRS) or physiological (PPG, EDA, EMG) signals reported notable inter-subject variability in pain perception and responses; these reported differences in neural and physiological responses affected the capacity of machine learning models to generalise across people 28 , 34 , 70 , 71 , 103 , 117 . Inter-individual differences often lead to model overfitting, which can be interpreted as the lack of model’s generalisability to give accurate predictions with new data 117 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future study, an extensive dataset including demographic and clinical data will be created using hospital databases along with the anesthesia depth reference (BIS) to develop a better machine learning model that could estimate the correct depth of anesthesia and provide a reliable and cost-effective monitoring solution to the staff. Additionally, deep learning has been proposed as a promising tool to achieve reliable detection of anesthesia, which deserves exploration based on multi-center, large-scale datasets [34].…”
Section: Future Workmentioning
confidence: 99%
“…For example, EDA can capture sympathetic changes related to pain, as it measures the sweat glad activity as response to pain ( 9 ). PPG can be used to measure the autonomic response through analysis of heart rate variability (HRV) ( 10 ). The respiratory system is also affected by a sympathetic nerves, which have a stimulating effect by increasing oxygen intake in the event of acute pain ( 11 ).…”
Section: Introductionmentioning
confidence: 99%